2018
DOI: 10.21107/infestasi.v14i2.4870
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tekanan Ketaatan, Pengetahuan, Dan Pengalaman Auditor Terhadap Audit Judgment

Abstract: <p><em>This research is quantitative research. The data used in this study is primary data by distributing questionnaires to public accounting firms domiciled in DKI Jakarta. The population in this study were auditors who worked in the Public Accounting Office. Questionnaires were distributed as many as 130 questionnaires and data that could be processed as many as 100 questionnaires. Data is processed using the help of SPSS 23. The purpose of this study is to examine the effect of auditor complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…When the difference in expectations occurs, the auditor will pressure the auditor to equalize expectations to arise between the auditor and the entity. This study's results support the results (Tampubolon, 2018;Putri, 2018), finding that compliance pressure has a positive and significant effect on audit judgment. Pertiwi & Budiartha (2017) the higher the auditor's compliance pressure, the less precise the audit assessment will be.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When the difference in expectations occurs, the auditor will pressure the auditor to equalize expectations to arise between the auditor and the entity. This study's results support the results (Tampubolon, 2018;Putri, 2018), finding that compliance pressure has a positive and significant effect on audit judgment. Pertiwi & Budiartha (2017) the higher the auditor's compliance pressure, the less precise the audit assessment will be.…”
Section: Discussionsupporting
confidence: 89%
“…Obedience pressure in the form of pressure from the agency and pressure from superiors can also affect the auditor's judgment. The research results by (Tampubolon, 2018;Putri, 2018) found that compliance pressure has a positive and significant effect on audit judgment. Pertiwi & Budiartha (2017) found that the higher the auditor's compliance pressure, the less precise the audit assessment will be.…”
Section: Introduction 12mentioning
confidence: 99%
“…Pada dasarnya seorang auditor harus mempunyai pengetahuan mengenai prinsip akuntansi, standar auditing serta industri klien yang didapat dari pendidikan formal, pengalaman, praktek audit dan pelatihan (Dethan, 2016;Sukmawati & Faisal, 2015). Pengetahuan seorang auditor menjadi kunci penting dalam membentuk suatu keputusan, disamping itu seorang auditor yang sanggup mengembangkan pengetahuan akan mengantongi wawasan yang sangat luas dalam dunia praktik akuntansi dan menguasai teknik audit dalam pembuatan judgment (Tampubolon, 2018). Pengetahuan yang terus dikembangkan dapat meningkatkan pemahaman intelektual yang baik dalam menyelesaikan tugas secara efektif dan menjadi kunci dalam pengambilan keputusan audit (Yendrawati & Mukti, 2015).…”
Section: Modal Manusiaunclassified
“…Pengajuan dari atasan dapat berupa anggaran waktu, tenggat waktu, dan justifikasi untuk melakukan penilaian. Sementara itu, tekanan dari klien, seperti tekanan pribadi, emosional atau keuangan, dapat mengurangi independensi auditor dan mempengaruhi kualitas audit dan penilaian auditor [13].…”
Section: Tekanan Ketaatanunclassified